Comparison of prokaryotic community structure from Mediterranean and Atlantic saltern concentrator ponds by a metagenomic approach - Fernández, Ana B.; Vera-Gargallo, Blanca; Sánchez-Porro, Cristina; Ghai, Rohit; Papke, R. Thane; Rodriguez-Valera, Francisco; Ventosa, Antonio (Frontiers in Microbiology, 2014)
We analyzed the prokaryotic community structure of a saltern pond with 21 % total salts located in Isla Cristina, Huelva, Southwest Spain, close to the Atlantic ocean coast. For this purpose, we constructed a metagenome (designated as IC21) obtained by pyrosequencing consisting of 486 Mb with an average read length of 397 bp and compared it with other metagenomic datasets obtained from ponds with 19, 33 and 37 % total salts acquired from Santa Pola marine saltern, located in Alicante, East Spain, on the Mediterranean coast. Although the salinity in IC21 is closer to the pond with 19 % total salts from Santa Pola saltern (designated as SS19), IC21 is more similar at higher taxonomic levels to the pond with 33 % total salts from Santa Pola saltern (designated as SS33), since both are predominated by the phylum Euryarchaeota. However, there are significant differences at lower taxonomic levels where most sequences were related to the genus Halorubrum in IC21 and to Haloquadratum in SS33. Within the Bacteroidetes, the genus Psychroflexus is the most abundant in IC21 while Salinibacter dominates in SS33. Sequences related to bacteriorhodopsins and halorhodopsins correlate with the abundance of Haloquadratum in Santa Pola SS19 to SS33 and of Halorubrum in Isla Cristina IC21 dataset, respectively. Differences in composition might be attributed to local ecological conditions since IC21 showed a decrease in the number of sequences related to the synthesis of compatible solutes and in the utilization of phosphonate.